Eficiência do hidrogel em mudas de maracujazeiro submetidas a diferentes lâminas de irrigação - PEREIRA, Marcia da Silva (Universidade Federal do Oeste do Pará, 2024)
The growth of passion fruit production is influenced by several factors that affect the longevity of the orchard, the productivity and quality of the fruits. Among the factors that promote negative effects on the development of passion fruit is water stress. In this scenario, the use of water seals has emerged on the market as an alternative to minimize problems linked to water deficiency. In this context, the present work aimed to evaluate the efficiency of the hydrogel in passion fruit seedlings subjected to different water depths. The experiment was installed in CRD, in the Vegetation House II of the Juruti/UFOPA University Campus. Seeds from the BRS Sol do Cerrado cultivar, developed by Embrapa's Passion Fruit Genetic Improvement Program (PMG), were used. 35 days after the start of germination in commercial substrate, the seedlings were transplanted into 3.6 liter pots using 200g of gravel at the bottom; and substrate containing 80% soil and 20% cattle manure; and hydrogel polymer applied in doses of 100% (3.0 g) and 0%. To evaluate the efficiency of the hydrogel, the experiment was conducted in a 2x2 factorial scheme, with the treatments distributed in: T1 – (0% hydrogel - 100% of water demand - DH); T2 - (100% hydrogel - 100% DH); T3 - (0% hydrogel - 50% DH); T4 - (100% hydrogel – 50% DH), with 7 repetitions per treatment. During the experiment, the parameters of number of leaves, plant height and stem diameter were evaluated weekly. At the end of the experiment, the variables of fresh and dry mass of the aerial part, fresh and dry mass of the root, root volume, Dickson Quality Index (DQI) and Relative water content in the plant (RCA) were measured. The data were analyzed and the means were compared using the Tukey test at 5% probability, using SISVAR software. In general, it was observed that the plants showed similar growth throughout the period evaluated in the experiment. However, treatments T1 and T2, which had a water demand of 100%, associated with the hydrogel, showed better development for some of the parameters evaluated, confirming the efficiency of the ideal use of irrigation sheets for the development of seedlings.